2007
DOI: 10.1080/15459620701358102
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Bitumen Fumes Using Two Fume Generation Protocols and Comparison to Worker Industrial Hygiene Exposures

Abstract: This study had two fundamental goals. The first was to collect sufficient quantities of bitumen fumes used in both the roofing and paving industry in the United States to do detailed chemical and biological testing in preparation for a two-year animal skin painting study on select samples. These bitumen fumes need to be similar to the fumes to which workers in these industries are actually exposed. In this first phase, bitumen from four geographical regions of the United States were selected, which produced bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 13 publications
0
18
1
Order By: Relevance
“…The higher the temperature of preparation of the bitumen emission condensates, the greater tumorigenic activity observed. Kriech et al (2007) showed that these emissions were not the same as worker exposures and that the high temperature and continuous agitation contributed to significantly higher levels of 4-6 ring PACs than seen in worker exposures. A follow-up mouse study was conducted in 1989 by Sivak et al on five fractions of this same fume condensate -with increasing polarity A, B, C, D and E. The carcinogenic activity was limited to Fractions B and C, which represented only 10.2% of the total fume condensate.…”
Section: Complex Petroleum Substancesmentioning
confidence: 93%
See 4 more Smart Citations
“…The higher the temperature of preparation of the bitumen emission condensates, the greater tumorigenic activity observed. Kriech et al (2007) showed that these emissions were not the same as worker exposures and that the high temperature and continuous agitation contributed to significantly higher levels of 4-6 ring PACs than seen in worker exposures. A follow-up mouse study was conducted in 1989 by Sivak et al on five fractions of this same fume condensate -with increasing polarity A, B, C, D and E. The carcinogenic activity was limited to Fractions B and C, which represented only 10.2% of the total fume condensate.…”
Section: Complex Petroleum Substancesmentioning
confidence: 93%
“…Much of the polycyclic aromatic compound (PAC) composition is in the form of alkylated species (primarily alkyl-naphthalenes, alkyl-fluorenes and alkyl-anthracenes) and includes sulfur heterocyclic materials (primarily alkyl benzothiophene and alkyl-dibenzothiophenes). The most prominent of the parent, unalkylated PACs detected in workplace exposures for paving and roofing workers include acenaphthene, anthracene, fluoranthene, fluorene, naphthalene, phenanthrene and pyrene (Kriech et al 2007;Cavallari et al 2012a). Normal paving worker exposures contain only trace levels of parent unalkylated PACs, primarily of the 2-and 3-ring variety.…”
Section: Complex Petroleum Substancesmentioning
confidence: 99%
See 3 more Smart Citations